A decadência das contribuições previdenciárias no âmbito das execuções instauradas pela Justiça do Trabalho - Suaiden, Chede Domingos (2010)
Many discussions are held about the statute of limitations on the collection of social security contributions when it is executed in the sphere of the Labor Courts. Often, based on the argument that the Social Protection System itself should be safeguarded, the juridical safety is relegated to second place. As this paper will show, said issue creates more unsafety to all citizens to the extent that the end is overestimated to the detriment of the means created with mechanisms of checks and balances to allow previous knowledge of the rules that will govern the social relations. Especially within the context of the Tax Law, the guidelines laid down by the Constituent Power must be carefully followed otherwise we may turn our legal system into a make-believe legal system. The purpose of this study lies in identifying the rules in the Constitution and in the ordinary law that govern the principle of the statute of limitations and further, if such rules change where such contributions are executed in the context of labor claims. To this end, an in-depth analysis is required. We intend to understand the constitutional limitation of the State itself when confronted with the limitations imposed by the Constituent Power. The pertinent legislation will be searched for the proper juridical vehicles able to introduce rules for the statute of limitations on the social security contributions, and any affront to said instructions by the lawmaker, should any unconstitutional law have been created on the pretext of protecting the collection of such contributions to finance the Social Security. At the end, the conclusion will demonstrate how the statute of limitations on social security contributions should be applied even where they are executed by the Labor Courts and indicate if the Brazilian lawmaker is alert to said fact